2009
DOI: 10.1007/978-3-642-02927-1_62
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Symbol Comparisons in QuickSort and QuickSelect

Abstract: We revisit the classical QuickSort and QuickSelect algorithms, under a complexity model that fully takes into account the elementary comparisons between symbols composing the records to be processed. Our probabilistic models belong to a broad category of information sources that encompasses memoryless (i.e., independent-symbols) and Markov sources, as well as many unbounded-correlation sources. We establish that, under our conditions, the average-case complexity of QuickSort is O(n log 2 n) [rather than O(n lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 14 publications
(18 reference statements)
4
57
0
Order By: Relevance
“…However, this cost involves various constants that depend on the source S (and possibly on the real α); these are precisely described in Theorem 2 and displayed in Figure 2. Here, for the QuickSelect algorithms, we prove all the results which were only stated in the extended abstract [26], and we exhibit the probabilistic features of the source which play a role in the analysis: each algorithm of interest is related to a particular constant depending on the source; this constant describes the interplay between the algorithm and the source and explains how the efficiency of the algorithm depends on the source.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, this cost involves various constants that depend on the source S (and possibly on the real α); these are precisely described in Theorem 2 and displayed in Figure 2. Here, for the QuickSelect algorithms, we prove all the results which were only stated in the extended abstract [26], and we exhibit the probabilistic features of the source which play a role in the analysis: each algorithm of interest is related to a particular constant depending on the source; this constant describes the interplay between the algorithm and the source and explains how the efficiency of the algorithm depends on the source.…”
Section: Introductionmentioning
confidence: 54%
“…The surprise is that there are cases where this upper bound is tight, as in QuickSort; others where both costs are of the same order, as in QuickSelect. In previous works [26,3], we have already shown that the expected cost of QuickSort is Θpn log 2 nq, not Θpn log nq, when all elementary operations-symbol comparisons-are taken into account. By contrast, we prove here that the cost of QuickSelect turns out to be Θpnq, in both the old and the new world, albeit, of course, with different implied constants.…”
Section: Introductionmentioning
confidence: 97%
“…This immediately implies the following: Corollary 1.1. All the expected running time bounds proved for quicksort in [5] and [14] carry over to mergesort with the constant for the leading term improved by a factor of 2 log 2 ≈ 1.39. Theorem 1.3.…”
Section: R(ϑ(w))mentioning
confidence: 97%
“…There are several reasons. Firstly, we can reprove some of the results in [5,14,4], arguably in a much simpler way. Secondly, such tries turn up in our analysis of mergesort.…”
Section: Random Stringsmentioning
confidence: 99%
See 1 more Smart Citation